2014
DOI: 10.1152/ajpregu.00212.2014
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of mTORC1 activation in acid-α-glucosidase-deficient cells and mice is ameliorated by leucine supplementation

Abstract: Pompe disease is due to a deficiency in acid-α-glucosidase (GAA) and results in debilitating skeletal muscle wasting, characterized by the accumulation of glycogen and autophagic vesicles. Given the role of lysosomes as a platform for mTORC1 activation, we examined mTORC1 activity in models of Pompe disease. GAA-knockdown C2C12 myoblasts and GAA-deficient human skin fibroblasts of infantile Pompe patients were found to have decreased mTORC1 activation. Treatment with the cell-permeable leucine analog l-leucyl-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 34 publications
4
16
0
Order By: Relevance
“…We here analyzed phosphorylation of 2 targets of mTORC1, S6K and 4E-BP1, by exposure to amino acids and insulin, and demonstrated that mTORC1 activation was significantly reduced in myocytes derived from Pom iPSC MyoD . This is consistent with recent reports of suppressed mTORC1 activation in fibroblasts from patients with IOPD 47 , GAA-knockdown C2C12 myoblasts, or GAA-KO mice 48 , 49 . In our study, responses to rhGAA treatment were different between S6K and 4E-BP1, which may be attributed to the more complicated regulation of phosphorylation of 4E-BP1 than that of S6K 50 .…”
Section: Discussionsupporting
confidence: 93%
“…We here analyzed phosphorylation of 2 targets of mTORC1, S6K and 4E-BP1, by exposure to amino acids and insulin, and demonstrated that mTORC1 activation was significantly reduced in myocytes derived from Pom iPSC MyoD . This is consistent with recent reports of suppressed mTORC1 activation in fibroblasts from patients with IOPD 47 , GAA-knockdown C2C12 myoblasts, or GAA-KO mice 48 , 49 . In our study, responses to rhGAA treatment were different between S6K and 4E-BP1, which may be attributed to the more complicated regulation of phosphorylation of 4E-BP1 than that of S6K 50 .…”
Section: Discussionsupporting
confidence: 93%
“…Reduced mTORC1 activity has been documented in fibroblasts from Pompe patients and in GAA KO muscle. 48 We, too, observe inhibition of mTORC1 activity in cultured murine KO myotubes and whole muscle from Pompe mice (unpublished data). The link between lysosomal glycogen over-accumulation and reduced mTORC1 activity is supported by the data showing that the deficiency of the putative lysosomal sugar transporter Spinster (Spin) leads to lysosomal accumulation of carbohydrates in the enlarged lysosomes and an mTORC1 dysfunction (lack of its reactivation after prolonged starvation).…”
Section: Calcium Homeostasismentioning
confidence: 84%
“…The information regarding mTOR signaling in Pompe muscle cells is limited to a recent finding of reduced insulin‐stimulated mTORC1 activation in two cellular models of Pompe disease—GAA‐knockdown C2C12 myoblasts and GAA‐deficient human fibroblasts from infantile Pompe patients (Shemesh et al , ). However, neither basal levels of mTOR activity nor the mechanism of mTOR dysregulation was evaluated in these models, which are quite different from the one used in this study—multinucleated KO myotubes displaying enlarged glycogen‐filled lysosomes and defective autophagy—the two major pathologies in the diseased muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data demonstrate that leucine enters the lysosome through the leucine transporter, which is recruited to the lysosomal membrane by the lysosomal protein LAPTM4b (Milkereit et al , ). Leucine supplementation has been recently proposed as a therapeutic approach for Pompe disease (Shemesh et al , ). Our data demonstrate the leucine‐mediated process of mTOR recruitment to the lysosome is already activated in the diseased Pompe muscle cells; therefore, pushing it further does not seem to make much sense, and may even be harmful in the long run.…”
Section: Discussionmentioning
confidence: 99%